Annona muricata prevent hepatic fibrosis by enhancing lysosomal membrane stability and suppressing extracellular matrix protein accumulation - Usunobun, Usunomena; Okolie, Ngozi (International Journal of Medicine, 2016)
Background: Hepatic fibrosis is a pre-pathologic state of cirrhosis, which plays a pivotal role in the pathogenesis of hepatocellular carcinoma (HCC). This study was carried out to evaluate the hepatoprotective effect of Annona muricata leaves on extracellular matrix (ECM) accumulation, lysosomal membrane integrity and liver damage in dimethylnitrosamine (DMN)-induced fibrotic rats.Methods: Healthy adult male wistar rats were divided into four groups. Group I rats received normal saline and served as control, Group II rats were administered 200mg/kg Annona muricata, Group III received 200mg/kg Annona muricata orally simultaneously with 10mg/kg DMN, Group IV received 10 mg/kg DMN without extract. DMN administered intraperitoneally was on first three days of each week for two weeks while Annona muricata was administered for 14 consecutive days. 24 hours after last administration, all animals were sacrificed and blood collected for serum analysis. Biochemical parameters such as lactate dehydrogenase (LDH), total bilirubin (TB), total protein (TP), and albumin (ALB) were estimated to assess liver function and synthetic ability while hyaluronic acid (HA) was determined to assess extracellular matrix (ECM) function. In addition, acid phosphatase (ACP) was estimated to assess lysosomal membrane stability/fragility.Results: Liver damage, decreased synthetic ability, lysosomal membrane fragility and altered ECM function were evident by an increase in the levels of LDH, TB, ACP and HA as well as a decrease in level of TP and ALB in sera of rats administered DMN compared to normal rats. However, simultaneous treatment with Annona muricata leaf extract significantly (p<0.05) reversed alterations in the above indices.Conclusion: This study suggests that Annona muricata leaf functions as a potent fibrosuppressant by suppressing ECM accumulation, enhancing lysosomal membrane stability and liver synthetic ability.